The Influence of the No Manu Foam Game on the Cooperation Skills of Group B Children - Kolo, Maria yosefina; Akbar, Mochamad Ramli; Asmah, Ayu (UNIB Press, 2024)
Early childhood's ability to work together is vital to building good relationships. Observations at Santa Maria 03 Malang Catholic School show children cannot cooperate properly while playing. This study aims to determine whether the Busa No Manu game affects group B children's ability to cooperate in the Catholic school of Santa Maria 03 Malang. The method used is experimentation with pre-test and post-test designs in one group. The study subjects consisted of 14 children who followed the game of foam No Manu. Data is collected through observations and assessments of cooperative capabilities before and after treatment. Before treatment, the child's average cooperative score was 0.107%, while after playing, the average score increased to 0.115%. Statistical analysis using the t-test showed a p-value < 0.05, indicating a significant improvement in the children's cooperative ability after playing. The results of the research showed that the Busa No Manu game was effective in improving the ability of children to cooperate. The conclusion of the research on the No Manu Foam Game applied to children in group B has a positive influence on children's cooperation skills. Keywords: Foam No Manu game; cooperative ability; Kindergarten; child cooperation